2023
DOI: 10.1371/journal.pntd.0011432
|View full text |Cite
|
Sign up to set email alerts
|

The species distribution and antimicrobial resistance profiles of Nocardia species in China: A systematic review and meta-analysis

Abstract: Background Nocardia species can cause local or disseminated infection. Prompt diagnosis and appropriate treatment of nocardiosis are required, because it can cause significant morbidity and mortality. Knowledge of local species distribution and susceptibility patterns is important to appropriate empiric therapy. However, knowledge on the epidemiology and antimicrobial susceptibility profiles of clinical Nocardia species remains limited in China. Methods The data of isolation of Nocardia species were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“… 41 Imipenem has varying sensitivity to various species of Nocardia , with a good sensitivity rate of 90.1% to N. cyriacigeorgica , while it showed a relatively low sensitivity rate to N. farcinica (45.5%). 41 For immunocompetent patients, a 6-month course of antibacterial treatment is generally recommended, whereas immunosuppressed patients or those with disseminated CNS lesions typically require at least 6–12 months of treatment. 5 The continuous presence or recurrence of Nocardia infection is often attributed to the use of insensitive antibiotics or inadequate treatment.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… 41 Imipenem has varying sensitivity to various species of Nocardia , with a good sensitivity rate of 90.1% to N. cyriacigeorgica , while it showed a relatively low sensitivity rate to N. farcinica (45.5%). 41 For immunocompetent patients, a 6-month course of antibacterial treatment is generally recommended, whereas immunosuppressed patients or those with disseminated CNS lesions typically require at least 6–12 months of treatment. 5 The continuous presence or recurrence of Nocardia infection is often attributed to the use of insensitive antibiotics or inadequate treatment.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…A study on the distribution of Nocardia species and drug resistance in China showed that TMP-SMX was the most active drug against Nocardia isolated in China, and it could be used as the primary drug for treating Nocardia infections even without species identification or antibiotic susceptibility testing. 41 Linezolid and amikacin are also effective drugs against most Nocardia species, with activity of 99.5% and 96.0%, respectively. 41 Imipenem has varying sensitivity to various species of Nocardia , with a good sensitivity rate of 90.1% to N. cyriacigeorgica , while it showed a relatively low sensitivity rate to N. farcinica (45.5%).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocardia species are gram-positive, aerobic, weakly acid-resistant actinomycetes that are widely distributed in natural environments such as soil, freshwater, and dust [1]. Nocardia is known to cause nocardiosis, a group of serious opportunistic infections that primarily cause lung and skin infections affecting individuals of varying immune status [2,3]. In recent years, there has been a notable increase in the number of reported Nocardia infections in both immunocompromised and immunocompetent populations [4,5], and lack of timely and accurate treatment can lead to worsening clinical symptoms and high mortality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is to improve the identi cation of Nocardia infections in clinical settings. Firstly, A summary of commonly isolated Nocardia species was conducted: N. farcinica is prevalent in China, South Africa, Belgium, and France [3,[19][20][21]; N. cyriacigeorgica is common in Spain and Iran [22,23]; and N. nova has the highest isolation rate in the United States and Australia [24,25]. Based on this valuable insight, our comprehensive study focused on these common species.…”
Section: Introductionmentioning
confidence: 99%